2017
DOI: 10.1097/ta.0000000000001276
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation for adult respiratory distress syndrome in trauma patients

Abstract: Therapeutic study, level V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 38 publications
1
59
0
1
Order By: Relevance
“…Physicians manage these thrombotic challenges with use of anticoagulants, most commonly systemic administration of heparin. However excess anticoagulation, particularly when administered systemically, may cause bleeding problems . In fact bleeding issues are the most common complication in extracorporeal membrane oxygenation (ECMO), occurring in between 10–30% of cases, and the thrombotic complications that anticoagulation is meant to blunt, commonly lead to reduced device lifespan .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians manage these thrombotic challenges with use of anticoagulants, most commonly systemic administration of heparin. However excess anticoagulation, particularly when administered systemically, may cause bleeding problems . In fact bleeding issues are the most common complication in extracorporeal membrane oxygenation (ECMO), occurring in between 10–30% of cases, and the thrombotic complications that anticoagulation is meant to blunt, commonly lead to reduced device lifespan .…”
Section: Introductionmentioning
confidence: 99%
“…However excess anticoagulation, particularly when administered systemically, may cause bleeding problems. 13,14 In fact bleeding issues are the most common complication in extracorporeal membrane oxygenation (ECMO), occurring in between 10-30% of cases, and the thrombotic complications that anticoagulation is meant to blunt, commonly lead to reduced device lifespan. 9,[14][15][16] The risks associated with limited device blood biocompatibility and the pharmacologic interventions utilized to address this limitation clearly restrict the broader adoption of life saving extracorporeal therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The mean injury severity score (ISS) for all trauma ECMO patients treated at our institution was slightly higher at 32. Robba et al recently presented a review of 16 studies with a total of 31 patients treated with ECMO after sustaining multitrauma (8). The median ISS in this review was found to be 66, however the ISS was available in only 5 of the 16 the studies.…”
Section: Discussionmentioning
confidence: 77%
“…Unfortunately, most of these studies include patients prior to the influenza pandemic of 2009, which led to rapid advances in ECMO technology, technique, and understanding. Robba et al recently presented a review of 16 studies with a total of 31 patients treated with ECMO after sustaining multitrauma (8). In some studies, the VA ECMO survival is reported as high as 41.2% (4) and yet in others survival is much less or zero (7).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, ECMO was not utilized in TBI patients because of the risk of cerebral bleeding related to the use of anticoagulation. Recently, some case reports and small case series have suggested a potential beneficial use of ECMO in TBI patients [41]. Surprisingly, nearly half of our respondents would use ECMO in TBI patients as rescue respiratory strategy.…”
Section: Rescue Strategies For Refractory Respiratory Failurementioning
confidence: 87%